The Access Code. The Review of the Monograph by M.A. Perepelkin “Khodivshie po mukam: ‛samarskii kod’ v trilogii A.N. Tolstogo” - Ksenia I. Morozova (Studia Litterarum)
The article represents a review on the monograph by M.A. Perepelkin “Khodivshie po mukam: ʽsamarskii kod’ v trilogii A.N. Tolstogo” (Samara, 2022). The aim of the Samara literary critic and local historian lays in the realistic representation of the narrative strategy of a writer. M.A. Perepelkin is the first researcher who has paid attention to certain “discrepancies” in the work and identified its unique “code.” The objectivity of the conclusions is verified by the wide range of factual materials (archival documents, memoirs, newspaper articles, etc.). Firstly, the edition has proved its novelty by introducing into scientific circulation the unique biographical facts about the writer himself with his close surrounding alongside with other bright contemporaries. Secondly, it is a development of brand new methodical approaches to the analysis of the interconnection between historical and literary memorу. The reviewer gives a brief description of chapters of the monograph paying special attention to the aspects which bear the greatest importance while confirming the value of the fundamental research conducted by M.A. Perepelkin. The author of the review comes to the conclusion that the monograph given should be considered as the main tool for forming and storing historical memory.